The Use of ICT Tools in the Creative Industries Sector in Poland: Selected Industry Profiles - Magdalena RATALEWSKA (Communications of International Proceedings, 2022)
The creative industries sector and its individual industries play an increasingly important role in the modern economy. In highly developed countries, it is one of the most dynamically growing areas of the economy. The activity of the creative industries sector leads to the manufacturing of a product whose added value is a unique, original idea related to the form and/or function of the product or the manufacturing technology and/or materials used. Thanks to this added value, the product becomes competitive with other products or services – due to its unique, distinctive character, functionality, aesthetics, or price. Companies operating in the creative industries sector seek not only new organisational solutions or ways to create an organisational climate conducive to the development of creativity but also infrastructure as well as IT and communication solutions that support its development. The aim of the article is to analyse the use of Information and Communication Technologies (ICT) in various areas of the company's operation depending on the industry and the size of the enterprise. The companies covered by the quantitative study belong to four industries of the creative sector: architecture and interior design, fashion and industrial design, programming and computer games, as well as advertising and related activities, and operate in the micro, small and medium-sized enterprise sector.
Keywords: ICT; SMEs; small businesses; creative sector; architecture and design; fashion and industrial design; programming and computer games; advertising and related activities